(untitled) (Economic studies journal, 2021)
Abstract This research aimed to identify the role of the capital standard provided by the customer as one of the basic Elements in (C5) as a model of the commonly used models to be applied when granting credit in reducing the creditRisk represented by the risk of delay in payment and the accumulation of debts facing credit institutions in generalAnd banks of Maserati particularly. Because of the nature of the research problem and the objectives, the descriptive Approach was adopted in order to achieve the research goal. The research population was the public commercial banks operating in the city of Maserati, namely (Al- Wanda Bank, Al-Jumhouria Bank, Al-Sahara Bank, and the branch of Libyan central Bank). The sixty one employees who involves in the decision-making process of granting credit were surveyed in order to gather the Research data, the questionnaire was the tool for data collection, and it was analyzed using the SPSS program. The research results proved that the studied commercial banks do not apply all the basic conditions that must be met in the client’s capital as a basic standard in the C5 model for granting credit, and it was found that theyDo not attach great importance to the paragraph on net working capital (as one of the dimensions of this criterion), Which must be taken into account when evaluating the credit capacity of the customer? Through the results that wereReached, a number of recommendations were offered, the most important of which was the need to train creditDepartment employees and develop their knowledge to use scientific methods and methods in evaluating clients andEnable them to use financial statements and their ability to conduct financial analysis on them to help credit decisionMakers, as well as that these dimensions represent consecutive steps that will lead to defects in one of them, to Defects in the results of the other elements of the model